Mining Functional Modules in Genetic Networks with Decomposable Graphical Models - Dejori, Mathäus; Schwaighofer, Anton; Tresp, Volker; Stetter, Martin (OMICS A Journal of Integrative Biology, 2004)
In recent years graphical models have become an increasingly important tool for the structural analysis of genome- wide expression profiles at the systems level. Here we present a new graphical modelling technique, which is based on decomposable graphical models, and apply it to a set of gene expression profiles from acute lymphoblastic leukemia (ALL). The new method explains probabilistic dependencies of expression levels in terms of the concerted action of underlying genetic functional modules, which are represented as so- called “cliques” in the graph. In addition, the method uses continuous- valued (instead of discretized) expression levels, and makes no particular assumption about their probability distribution. We show that the method successfully groups members of known functional modules to cliques. Our method allows the evaluation of the importance of genes for global cellular functions based on both link count and the clique membership count.